MEDIEVAL EASTERN PHILOSOPHY AND CHARACTERISTICS OF THE RENAISSANCE - Mustafayev Jafar Shomirzayevich; Abdulla Jabborov Akbar o‘g‘li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article provides a comprehensive scientific exploration of the development and historical stages of philosophy, focusing on the differences between Eastern and Western philosophies and the influence of Eurocentrism. It examines the uniqueness of Eastern philosophy, its historical and cultural sources, and its contribution to world civilization. The reception and interpretation of medieval Eastern philosophy in the West are discussed. The article also emphasizes the need to re-evaluate Eastern philosophy from an objective and scientific perspective.